Active modification of cavity nest‐entrances is a common strategy in arboreal ants - Priest, Galen V.; Camarota, Flávio; Vasconcelos, Heraldo L.; Powell, Scott; Marquis, Robert J. (Biotropica, 2021)
The majority of tropical arboreal ant species nest in tree cavities. These cavities, often produced initially by wood‐boring beetles, can be in live or dead wood and represent long‐lasting and highly defensible nesting resources. Yet the size of cavity entrances can constrain their use. Active entrance modification may be an effective way to overcome this constraint. Here, we conduct the first systematic study of nest‐entrance modification in an arboreal ant community. Using field experiments deployed across a number of tree species, we show that 14% of 2631 experimental cavities were modified by either enlargement, or reducing entrance size by construction. Entrance modifications, which were made by a majority (18/29 species) of the species that occupied experimental nests, used a variety of construction techniques and materials. Combined, these modifications were context‐dependent with respect to available entrance sizes: Enlargement was more common when the diversity of available entrance sizes was limited, whereas reduction was more prevalent when the diversity of entrance sizes was higher. Nevertheless, the context of tree species identity did not significantly influence the number of modified cavities or the construction materials. Overall, we show that nest‐entrance modification is a widespread, active, and context‐dependent strategy in the nesting ecology of arboreal ants. Most tropical arboreal ant species nest in tree cavities, often produced by wood‐boring beetles, which can be in live or dead wood and represent long‐lasting and highly defensible nesting resources. Here, we conduct the first systematic study of nest‐entrance modification in an arboreal ant community using field experiments. Overall, we show that nest‐entrance modification is a widespread, active, and context‐dependent strategy in the nesting ecology of arboreal ants.